Chicken IRF10 suppresses the cGAS-STING-IFN antiviral signaling pathway by targeting IRF7 - Jiang, Sen; He, Jingyu; Wang, Kun; Lv, Mengjia; Han, Hongjian; Sun, Bingjie; Chen, Nanhua; Zheng, Wanglong; Zhu, Jianzhong (Frontiers in Immunology, 2026)
IntroductionThe innate immune cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING)-interferon (IFN) signaling axis is a cornerstone of antiviral innate immunity in chickens, with chicken interferon regulatory factor 7 (chIRF7) serving as the principal transcription factor downstream chSTING to initiate type I IFN production. Although the chicken interferon regulatory factor (IRF) family consists of eight members, the roles of those beyond chIRF7 in this pathway remain largely unexplored.MethodsSystematic screening was performed to analyze the roles of chicken IRF family members in the cGAS-STING-IFN antiviral signaling. Combined molecular biological and biochemical methods were utilized to explore the action mechanism of chIRF10 as a negative regulator of cGAS-STING-IFN antiviral signaling pathway in transfected cells and gene knockout cells, with or without different virus infections.ResultsThe chIRF10 was identified as a potent negative regulator of chicken cGAS-STING-IFN antiviral signaling. Mechanistically, chIRF10 mediated suppression required its IRF associated domain (IAD) but not its DNA binding domain (DBD). chIRF10 inhibited IFN activation triggered by cGAS-STING, as well as by the downstream kinases TBK1/IKKε and the transcription factor IRF7. Importantly, chIRF10 physically interacted with chIRF7 via its IAD, impairing chIRF7 dimerization and activation.DiscussionCollectively, these findings unveil a novel immunoregulatory function of chIRF10 and delineate a previously unrecognized mechanism fine-tuning the chicken cGAS-STING-IFN antiviral pathway, offering potential insights for developing interventions against avian viral diseases.